2014
DOI: 10.2217/imt.14.76
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Immunological Aspects of Exercise in Chronic Diseases

Abstract: Physical inactivity and sedentary lifestyles are believed to be independent risk factors for the occurrence of numerous diseases, including, obesity, Type 2 diabetes, metabolic syndrome, cardiovascular disease, cancer and mental health, all leading to substantial morbidity and/or premature death. It has been found that regular exercise, is associated with better quality of life and health outcomes, and reduces the risk of cardiovascular disease and cancer. Here, we review the effects regular exercise has on me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 119 publications
(90 reference statements)
1
26
0
Order By: Relevance
“…An inverse correlation between physical activity and cancer has been demonstrated in many recently published studies as well: Apart from the association between physical activity and an overall healthy lifestyle (especially in relation to reduced body weight and fatness), physical activity might reduce cancer risk also through the induction of epigenetic modifications [44][45][46][47][48][49][50]. The inverse correlation between fruit/vegetable consumption and cancer risk is well established: these foods harbor many protective factors such as polyphenols, flavonoids and fibers which are known to blunt cancer development [33,[51][52][53][54][55][56][57][58][59].…”
Section: Discussionmentioning
confidence: 95%
“…An inverse correlation between physical activity and cancer has been demonstrated in many recently published studies as well: Apart from the association between physical activity and an overall healthy lifestyle (especially in relation to reduced body weight and fatness), physical activity might reduce cancer risk also through the induction of epigenetic modifications [44][45][46][47][48][49][50]. The inverse correlation between fruit/vegetable consumption and cancer risk is well established: these foods harbor many protective factors such as polyphenols, flavonoids and fibers which are known to blunt cancer development [33,[51][52][53][54][55][56][57][58][59].…”
Section: Discussionmentioning
confidence: 95%
“…It is believed that a low intensity of everyday activity and a sedentary lifestyle constitute an independent risk of diseases known as "sedentariness" (such as diabetes, obesity or metabolic syndrome). A longitudinal Canadian study of 17,013 people aged over 12 years demonstrated that those who were inactive for a longer time span were 50% more likely to die prematurely in comparison with those who spent shorter periods of time in a sitting position [36].…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity has anti-inflammatory effects. 52 In view of this phenomenon, a reduced risk for MC in exercising individuals could hypothetically be expected. However, this was not the case in the present cohort.…”
Section: Discussionmentioning
confidence: 99%